Central, provincial, and municipal government policy in the Netherlands and the impact on firm migrations - Piet Pellenbarg; Cees-Jan Pen (European Regional Science Association (ERSA), 1998)
Since the nineteeneighties the study of firm migration has become a full-grown part of Economic Geography in The Netherlands. For the Faculty of Spatial Sciences in Groningen, the study of firm migration is one of its key research issues. Therefore firm migration is an essential element of its research program "demography of firms and the space economy". In this programm attention is focused on the spatial dimensions of processes of the birth, death and relocation of firms, as well as growth and shrink of firms. In the future the Faculty will investigate the trends in firm migration in other European Union Countries. First, the authors will present some theoretical backgrounds and recent information of the most important push, pull, keep and reject factors which determine why firms decide to relocate or not to relocate. The most important factors are space for expansion,a representative location, parkingspace and attainability by car. This introduction is followed by an overview of Dutch Government policy and its influence on firm migration. The recent study from the Ministry of Economic Affairs 'Ruimte voor Economische Dynamiek' (Space for economic dynamism)'(1997) emphasizes the importance of creating enough space for economic activities to sufficient accommodations for further employment growth. The biggest problem for the Dutch Government policy is to make a well-considered choice between space for living, working, infrastructure, nature and recreation in a rather crowded national space (especially in the west of The Netherlands). The authors give a brief description of the most important policy documents from the Ministries of Economic Affairs, Spatial and Environmental Planning, Infrastructure and Internal Affairs and the possible consequences in relation to firm migration. This section ends with an analysis of the contradictions in the Government policy and the influence on firm migration. The second section will provide quantative data regarding firm migration in The Netherlands. There are several statistical databases regarding the quantity, structure, spatial patterns and labour market effects of firm migration in The Netherlands. After the description of the most important backgrounds of firm mobility and relevant spatial Government policy in the preceding section, the authors will present some figures of firm migration in the years 1992-1995 on different spatial levels. These figures will show the increasing pressure on industry, wholesale trade and business services regarding business areas in the Randstad (the west of The Netherlands) and the growing tendency of these firms to migrate to business areas in the intermediate provinces like Noord-Brabant (in the south) and Gelderland (in the east). At the end the authors compare and relate the information of the two sections and give some recommendations for Dutch Government policy in the future.
Keywords: 330